Human blood test based on surface‐enhanced Raman spectroscopy technology using different excitation light for nasopharyngeal cancer detection. Issue 9 (18th October 2019) - Lin, Huijing; Zhou, Jiahui; Wu, Qiong; Hung, Tsung‐Min; Chen, Weiwei; Yu, Yun; Chang, Joseph Tung‐Chieh; Pan, Jianji; Qiu, Sufang; Chen, Rong
Abstract : Nasopharyngeal carcinoma (NPC), a kind of squamous cell carcinoma, occurs in the top and the side wall of nasopharyngeal, which harms human health and life. In this study, a novel blood test (SERS) was carried out for 30 NPC patients and 30 normal ones. Using multi‐variate statistical analysis for spectral data, the diagnostic sensitivities of 89.3% (50/56) and 85.7% (48/56) can be achieved for 633 and 785 nm exciting wavelength, respectively. Also corresponding specificities are 71.4% (41/56) and 78.6% (44/56), respectively. These results demonstrated that the two kinds of excitation wavelength all have the feasibility of obtaining high‐quality SERS spectra to differentiate cancer from normal samples. Furthermore, the performance of the SERS test with 785 nm wavelength excitation is nearly equal to the SERS experimental effect under 633 nm wavelength excitation for NPC detection.